Analisis SWOT pada Kawasan Wisata Pantai Ria Ende - Simo, Maria Novtasia; Langga, Lambertus; Dua Mea, Maria Helena Carolinda (Program Studi Manajemen Universitas Flores, 2021)
The purpose of this research is to know how to manage strategies in developing the tourism sector at Ria Beach. The type of research is descriptive research, namely describing, explaining and implement a phenomenon that occurs in an object and its data is qualitative, namely data that is described in words or sentences according to categories to obtain conclusion. The analysis used is SWOT analysis (strength, weakness, opportunities, threats). The results of this study show the analysis of EFAS and IFAS SWOT in the Ria Beach Tourism Area is a growth strategy where Cultural tourism in the village is in an advantageous position because have more dominant advantages and strength. SWOT matrix results shows that there are four maun development strategies that can implemented at Ria Beach including optimization strategis cultural tourism management, home based potential optimization strategy enterpises on Ria Beach to support tourism activities, utilixation intangible culture on Ria Beach as a product of cultural tourism and management of tangible cultural assets on Ria Beach through cooperation opportunites